The Russian American Relations since the Collapse of the Soviet Union: the international and political journal - م.م. حسام محمد خضير; م.م. حسين علي صبري (The International and Political Journal, 2025)
The Russian American relations have been witnessing continuous tension in recent years. This is due to disagreements over some global issues. Perhaps the new Ukrainian crisis is one of the most prominent of these issues at the present time. In this research, we tried to trace the foreign policy of the two countries in order to identify the origin of the problem of not reaching settlements. Therefore, we addressed Russian American relations in the era immediately following the collapse of the Soviet Union, i.e. the nineties of the last century, and then the period during which the Russian Federation witnessed a noticeable change in its foreign policy and international relations. Several possible future scenarios were put forward regarding the fate of relations between the two countries, and we preferred one of these scenarios, which indicates the continuation of stagnation in the aforementioned relations in light of the continuation of the Russian military operation in Ukraine, which began in February 2022.